2020
DOI: 10.1158/0008-5472.can-19-3819
|View full text |Cite
|
Sign up to set email alerts
|

Drug Sensitivity and Allele Specificity of First-Line Osimertinib Resistance EGFR Mutations

Abstract: ◥Osimertinib, a mutant-specific third-generation EGFR tyrosine kinase inhibitor, is emerging as the preferred first-line therapy for EGFR-mutant lung cancer, yet resistance inevitably develops in patients. We modeled acquired resistance to osimertinib in transgenic mouse models of EGFR L858R -induced lung adenocarcinoma and found that it is mediated largely through secondary mutations in EGFR-either C797S or L718V/Q. Analysis of circulating free DNA data from patients revealed that L718Q/V mutations almost alw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Patients typically have more concomitant genetic mutations and greater tumor heterogeneity after multiple treatments, which is an important reason for the discrepancy between cell assays and clinical results. Interestingly, afatinib, which is also a 2G TKI, showed good tumor control not only in in vitro cellular assays (5) on L718X/ L792X mutations but also in clinical application of L718X mutation according to several case reports (Supplementary Table 2) (16)(17)(18)(19)(20). Molecular structural models showed that, unlike dacomitinib, no clashes or spatial conflicts between afatinib in its L858R-bound orientation and the L718Q/V sidechain were observed (17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Patients typically have more concomitant genetic mutations and greater tumor heterogeneity after multiple treatments, which is an important reason for the discrepancy between cell assays and clinical results. Interestingly, afatinib, which is also a 2G TKI, showed good tumor control not only in in vitro cellular assays (5) on L718X/ L792X mutations but also in clinical application of L718X mutation according to several case reports (Supplementary Table 2) (16)(17)(18)(19)(20). Molecular structural models showed that, unlike dacomitinib, no clashes or spatial conflicts between afatinib in its L858R-bound orientation and the L718Q/V sidechain were observed (17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models are a key system for the advancement of our understanding of lung cancer targeted therapy resistance 11,[19][20][21] . However, recent findings demonstrate that these models lack the mutational heterogeneity present in human tumours [22][23][24] .…”
Section: Apobec3b Is Detrimental At Tumour Initiationmentioning
confidence: 99%
“…Similar results were described with erlotinib and afatinib in mice models. 51 Many other EGFR mutations have been described in patients progressing on osimertinib. Similarly to what has been described for the C797S mutation, some of these mutations have been found to respond to EGFR TKI in cellular models.…”
Section: Egfr Mutationsmentioning
confidence: 99%
“…52 In vitro, combination of first-line osimertinib and erlotinib prevented the emergence of secondary EGFR mutations. 51 The objective response rate of osimertinib in combination with gefitinib in EGFR inhibitor-naïve advanced EGFR mutant lung cancer is being investigated in the NCT03122717 phase 1/2 trial (Table 3).…”
Section: Egfr Mutationsmentioning
confidence: 99%